إشكالات البطاقة الائتمانية في المصارف الإسلامية في سلطنة عمان وماليزيا : دراسة فقهية مقارنة - سلماني، جاسم بن زاهر بن حمود (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
Credit card is among the Islamic financial products that is highly profitable to Islamic banking, although the Islamic jurists who sit in the Shariah boards differ in the modus operandi of its adaptation by the Islamic jurisprudence. This is so because the Malaysian Islamic banks adapted it based on the systematic financial securitization contract (tawarruq masrifi muntazam), but Islamic banks in Oman utilize the interest-free micro loans contract. There are still many problems in both means of adaptation that unless if addressed, will put a Muslim in questioning position that requires explanation. This is because of the possibility that the means adapted might still contain the suspicious element of usury (riba) that a normal true Muslim will strive to avoid because of the punishment that Allah the Al-Mighty warns those who are involved in it. Among the problematic matters that were central in many discussions are the imposing of fees for subscription, renewal, replacing and cash withdrawal, whereas the percentage is not lump sum. This is the same in the problems related to Islamic Jurisprudence that debated about the ruling of the purchase of gold and silver using the credit card, especially when the exchange of items does not happen at the selling place; this is because gold and silver are among the six types of goods that were conditioned by the Prophet PBUH to fulfill the two conditions of being represented and being exchanged at the selling place. Among other problems addressed by the study is the problem of gifts that are given by the banks to the card holders, the profit it make from the merchant and its means of adaptation to the Islamic requirements. The researcher also discusses the means in Islamic jurisprudence to adapt such financial products and the differences in opinions regarding the matter. This is done through the descriptive method in extracting the Islamic rulings from the views of the Islamic school of thoughts and the financial application. Subsequently, the relevant Islamic ruling to the application is concluded. In conclusion, the researcher presents several results and recommendations related to issue of credit card that would help the Sharia authorities in the Islamic banks to address this matter through the issues in Islamic Jurisprudence that were presented. Among the suggestions are; that members of Sharia' boards need to resolve some of the issues found in the financial application and the need for the bank to recognize the assets that are entrusted to the Islamic banks to issues this card to enable the evaluation of these banks which normally do not provide any reason in charging the rate or amount to the card holder. In addition, the recommendations will also be forwarded to the Islamic banks in Malaysia and the Sultanate of Oman.